PENGARUH QUALITY OF WORK LIFE TERHADAP KINERJA DOSEN DI LINGKUNGAN UNIVERSITAS LANCANG KUNING (DENGAN TEORI LMX SEBAGAI MODERASI) - Lubis, Nurhayani; Hardi, Hardi; Maryanti, Sri (Komunitas Manajemen Kompetitif, 2023)
This study was intended to determine the effect of Quality of Work Life (QWL) with the LMX variable as a moderating variable on the performance of lecturers at Lancing Kuning University. There are 4 hypotheses in this study. The results of data analysis from path analysis processing show that for hypothesis 1 the work environment influences the performance of lecturers in the Unilak environment. The reward system variable hypothesis has no effect on lecturer performance variables, hypothesis 2 is not accepted. For the third hypothesis, it can be concluded that the reward system through LMX does not affect the performance of lecturers at the Lancang Kuning University environment. And for the fourth hypothesis it is concluded that the work environment through LMX does not affect the performance of lecturers at the Lancang Kuning University environment.